Cox-2 inhibition activities of creams containing anguilla bicolor and sea cucumbers extract on croton oil induced inflammation in mice - Heru Sasongko; Waliyyin Razan Qanit; Raka Sukmabayu W.S; Agung Putu S.P.Kristyawan; Nining Sugihartini; Wisnu Kundarto; Dian Eka Ermawati (Universitas Ahmad Dahlan, 2020)
The fatty acids, like EPA and DHA, were known as anti-inflammation. It works on inflammatory tissue, brought by edema plasma, and changed into resolvins, protectins, and maresins by the enzyme reaction. Anguilla bicolor and Sea cucumber fish are known to contain EPA and DHA. This study analyzes the inhibition Cox-2 effect of the combination of Anguilla bicolor oil with Sea cucumber extract as an active ingredient in a cream preparation. This experiment used 7 groups of male BALB/C strain mice: normal control; negative control; positive control; A. bicolor oil cream; H. leucospilota extract cream; a combination of A. bicolor : H. leucospilota (2:1) cream; a combination of A. bicolor : H. leucospilota (1:2) cream. The anti-inflammatory activity was evaluated by the amount of inflammatory cell, the thickness epidermis, and the amount of cell expression COX-2Â on mice's back skin tissue induced by croton oil (0,1 %). After 3 days, histopathological skin tissues were made. The data were analyzed statistically by One Way ANOVA followed by LSD to know each group's differences at a significance level of 0.05. The experiment results showed that the formula with the best anti-inflammatory activities is the combination of A. bicolor and H. leucospilota (2:1) cream.Â The decrease of the amount of inflammatory cell (75.97%), the thickness of the epidermis (43.88%), and the amount of COX-2 cell expressions (60.52%) from the formula did not differ significantly with the positive control (p>0,05). It can be concluded that A. bicolor and H. leucospilota have anti-inflammation activity based on the experiment results.